2010
DOI: 10.1111/j.2042-3292.2010.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of an absorbable bone screw as a transphyseal bridge for the correction of fetlock varus deviations in six foals

Abstract: Summary This report describes and evaluates the use of a single‐positional absorbable screw (Smart Screw)1 as a temporary transphyseal bridge of the lateral aspect of the distal metacarpus in 6 foals with fetlock varus deformities. Using radiographic and visual assessments, an improvement in the severity of the deviation was identified in all cases. There were no complications encountered during screw placement or post operatively. The use of absorbable screws in the treatment of angular limb deformities in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…They concluded that bioabsorbable screws used to stabilise a fissure created from the sagittal ridge to middle-diaphysis of the distal third metacarpal/metatarsal bone were inferior to those made of stainless steel in achieving stability of the repair construct [10]. Wall et al [11] reported successfully using bioabsorbable screw to bridge the physis of long bones in foals as a means of correcting angular limb deformities. Pyles et al [12] investigated the efficacy of using a bioabsorbable screw to repair an induced fracture in the proximal sesamoid bone, while Mageed et al [13] reported using bioabsorbable screws to treat a splint bone fracture.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that bioabsorbable screws used to stabilise a fissure created from the sagittal ridge to middle-diaphysis of the distal third metacarpal/metatarsal bone were inferior to those made of stainless steel in achieving stability of the repair construct [10]. Wall et al [11] reported successfully using bioabsorbable screw to bridge the physis of long bones in foals as a means of correcting angular limb deformities. Pyles et al [12] investigated the efficacy of using a bioabsorbable screw to repair an induced fracture in the proximal sesamoid bone, while Mageed et al [13] reported using bioabsorbable screws to treat a splint bone fracture.…”
Section: Introductionmentioning
confidence: 99%
“…In equine orthopaedic surgery, absorbable implants made of synthetic polymers, such as polyglycolide, poly L-lactic acid (PLLA) or poly-dioxanone, have been described for fracture fixation, angular limb deformities correction and bone grafting. [14][15][16] A number of ceramic analogues of bone (e.g. hydroxyapatite, tricalcium phosphate) have shown promise because they have good tissue compatibility and bond directly to native bone without an intermediary layer of connective tissue.…”
mentioning
confidence: 99%